Pratiques langagières et glottophobie dans la ville de Bejaia : quand la langue est au service de la discrimination - Lydia Benbelaid (OpenEdition, 2020)
We are interested here in the glottophobic behaviors of the townspeople of Bejaia towards the newcomers. This glottophobia reflects a new relationship of the individual to the language and reveals the tensions between the city’s inhabitants. Through a sociolinguistic approach, we tried to understand this phenomenon and measure its extent. Indeed, our field survey allowed us to discover a deep discomfort between the inhabitants of the city, and a great intra-urban divide. This study shows glottophobic behaviors fully assumed and justified by a legitimacy to occupy space.